MEMAHAMI (MEMBANGUN) KONSEP DENGAN CARA BELAJAR KONSTRUKTIVIS DITINJAU DARI KREATIVITAS KEMAMPUAN BERPIKIR LOGIK DAN KEMAMPUAN BERPIKIR ABSTRAK (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The aim of this research is to know about how far the differences in understanding (determining) of physics concepts between the constructivist and behaviorist learning reviewed with creativity variable, logical and theoretical thinking ability. With a quasi experiment redesign method, its giving a different treatments that is they way of behaviorist and constructivist learning to the student of Physical Education in JPMIPA FKIP amount 49 students in third semester of 2010/2011 academic year with subject of Modern Physics. The instrument of this study are creativity tests, logocal thinking ability, theoretical thinking ability and comprehensive test (determining) of the concept and all instruments have been tested the reliability and validity. The finding in this study is discrepancy in understanding the concepts of modern physics which is significant between constructivist and behaviorist learning. They way of constructivist learning is better than behaviorist.